(untitled) - Murray, Kayleigh

The applicability of radiocarbon dating to understanding lifespan and mortality patterns in the quiver tree, Aloidendron dichotomum (Masson) Klopper & Gideon F.Sm. (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.